SILICIFIED MICROFOSSILS FROM THE VENDIAN YUDOMA GROUP, THE UCHUR-MAYA REGION OF SIBERIA: FACIES DEPENDENCE AND BIOSTRATIGRAPHIC POTENTIAL - Sergeev V.N. (My University, 2002)
Microbiota from cherts of the Vendian Yudoma Group, the terminal one in succession of Precambrian deposits of the Uchur-Maya region, southeastern Siberia, is described and analyzed. Dominant in the Yudoma microbiota are remains of morphologically simple filamentous and coccoidal microorganisms, mainly of cyanobacteria. Acritarchs of complex morphology, which have been described from Vendian deposits of some other regions (the so-called Pertatataka assemblage), are lacking in the studied cherts. In its general composition, the Yudoma microbiota resembles other assemblages of Proterozoic silicified microfossils representing remains of morphologically simple microorganisms conservative in the evolutionary aspect. Main factors that controlled its composition were the shallow-water facies affinity of host deposits and taphonomic peculiarities of fossilization, though the Upper Vendian level of host deposits defined by chemostratigraphic data was likely of a some significance as well, because the acritarch assemblages of the Pertatataka type are widespread in the Lower Vendian deposits only. Described in the paper are 20 species of 16 microfossils' genera, the new species Osculosphaera tarynnachia sp. nov. included.
Keywords: Vendian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский